Defective skeletogenesis and oversized otoliths in fish early stages in a changing ocean - Pimentel, Marta S. (2014)
Early life stages of many marine organisms are being challenged by rising seawater temperature and CO(2) concentrations, but their physiological responses to these environmental changes still remain unclear. In the present study, we show that future predictions of ocean warming (+4 degrees C) and acidification (DeltapH=0.5 units) may compromise the development of early life stages of a highly commercial teleost fish, Solea senegalensis. Exposure to future conditions caused a decline in hatching success and larval survival. Growth, metabolic rates and thermal tolerance increased with temperature but decreased under acidified conditions. Hypercapnia and warming amplified the incidence of deformities by 31.5% (including severe deformities such as lordosis, scoliosis and kyphosis), while promoting the occurrence of oversized otoliths (109.3% increase). Smaller larvae with greater skeletal deformities and larger otoliths may face major ecophysiological challenges, which might potentiate substantial declines in adult fish populations, putting in jeopardy the species' fitness under a changing ocean.